Fragilidade ambiental no baixo curso da bacia hidrográfica do Rio Aracatiaçu -Ceará - Sales, Licia Benicio (2019)
This study addresses the issue of environmental fragility in a watershed on the coast of Ceará. The different types of land use and cover that are factors that trigger degradation processes in watersheds intensify environmental fragility. The low course of the Aracatiaçu River basin was conceived as a territorial management and planning unit, where the population growth in urban centers, the increase in the flow of people, goods and capital with the construction of access highways and strategic location is evident, in the construction of wind farms. The conceptual and methodological bases are based on an integrated landscape conception that establishes physical-environmental / socioeconomic relations, allowing identifying, characterize and delimit the environmental systems present in the watershed. The objective of this research is to analyze the environmental fragility of the Aracatiaçu - Ceará River low course due to the natural vulnerability of the environmental systems and the different types of use and occupation. The use of the environmental fragility methodology allowed identifying the potentialities and limitations of the environmental systems and the degree of anthropic intervention in the landscape. The low course of the Aracatiaçu River Basin has 690 km², drains all or part of the municipalities of Amontada, Itarema and Itapipoca located in the northern portion of the state of Ceará. Low development, technology deficiency in the realization of the main economic activity, agriculture, lack of basic infrastructure for the inhabitants, poor supervision of environmentally compromising activities, this scenario contributes to the increase of environmental fragility. The study also presented possible scenarios of environmental systems based on environmental appropriation today and guidelines